An integrated high-resolution mapping shows congruent biodiversity patterns of Fagales and Pinales - Lyu, Lisha; Leugger, Flurin; Hagen, Oskar; Fopp, Fabian; Boschman, Lydian M.; Strijk, Joeri Sergej; Albouy, Camille; Karger, Dirk N.; Brun, Philipp; Wang, Zhiheng; Zimmermann, Niklaus E.; Pellissier, Loïc (New Phytologist, 2022)
Summary The documentation of biodiversity distribution through species range identification is crucial for macroecology, biogeography, conservation, and restoration. However, for plants, species range maps remain scarce and often inaccurate. We present a novel approach to map species ranges at a global scale, integrating polygon mapping and species distribution modelling (SDM). We develop a polygon mapping algorithm by considering distances and nestedness of occurrences. We further apply an SDM approach considering multiple modelling algorithms, complexity levels, and pseudo-absence selections to map the species at a high spatial resolution and intersect it with the generated polygons. We use this approach to construct range maps for all 1957 species of Fagales and Pinales with data compilated from multiple sources. We construct high-resolution global species richness maps of these important plant clades, and document diversity hotspots for both clades in southern and south-western China, Central America, and Borneo. We validate the approach with two representative genera, Quercus and Pinus, using previously published coarser range maps, and find good agreement. By efficiently producing high-resolution range maps, our mapping approach offers a new tool in the field of macroecology for studying global species distribution patterns and supporting ongoing conservation efforts.